STRATEGIES TO DEVELOP ARGUMENTS IN ACADEMIC WRITING BY STUDENTS OF GRADUATE PROGRAM IN INDONESIAN LANGUAGE EDUCATION SEBELAS MARETUNIVERSITY - Masithah Mahsa; Budhi Setiawan; Muhammad Rohmadi (Center of Language and Cultural Studies [CLCS], 2017)
There is a relationship between pattern of arguments in an academic writing and obstacles faced in writing process. This study aims to figure out the strategies to develop arguments in writing a scientific article used by the students of Graduate Program in Indonesia Language Education Sebelas Maret University. The study focuses on obstacles in writing the scientific article, and the strategies how students overcome the problem. This study is a qualitative descriptive research. The instruments were documents and interview sheet that was delivered to the author of the article. In collecting the data, the researcher used purposive sampling technique. The researcher used interactive analysis technique in order to analys the content of the data. Findings of this study showed that there were two obstacles and solution in arranging the arguments, they were internal and external aspect.